Theo dõi tình trạng dinh dưỡng và sức khoẻ của trẻ thừa cân béo phì tại Hà Nội - Lê, Thị Hải (2011)
Tác giả: Lê Thị Hải, ThS; Nguyễn Thị Lâm, TS; Nguyễn Thanh Hà, TS; Nguyễn Lương Hạnh, BS -- Từ khóa: Thừa cân; Béo phì; Trẻ em